1992
DOI: 10.1017/s0033291700030439
|View full text |Cite
|
Sign up to set email alerts
|

Why people with probable minor psychiatric morbidity consult a doctor

Abstract: SYNOPSISThis epidemiological investigation examines factors determining medical consultation in people with probable minor psychiatric morbidity. About 54% of people with probable minor psychiatric morbidity and about 23% of the (numerically much greater) remainder with lower probability of psychiatric morbidity consulted a doctor, usually a primary care physician, in the two weeks prior to a research interview. Medical consultation rates were higher in females than in males.The dominant finding was that in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…However, in this study comparisons were performed on samples stratified by attendance rate, not allowing a direct confrontation with our findings. Vazquez-Barquero et al (1992) investigated the joint effects of physical illness and sociodemographic variables on medical consultation by subjects with emotional distress, and found that physical illness emerged as the major single determinant of medical consultation in women, while in men it exerted its effect through an interaction with lower educational level. It was an unexpected finding that, in our study, physical health status was not confirmed by logistic regression analysis as a predictor of GP consultation.…”
Section: Physical Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this study comparisons were performed on samples stratified by attendance rate, not allowing a direct confrontation with our findings. Vazquez-Barquero et al (1992) investigated the joint effects of physical illness and sociodemographic variables on medical consultation by subjects with emotional distress, and found that physical illness emerged as the major single determinant of medical consultation in women, while in men it exerted its effect through an interaction with lower educational level. It was an unexpected finding that, in our study, physical health status was not confirmed by logistic regression analysis as a predictor of GP consultation.…”
Section: Physical Illnessmentioning
confidence: 99%
“…It was an unexpected finding that, in our study, physical health status was not confirmed by logistic regression analysis as a predictor of GP consultation. This discrepancy might be due to the stricter criteria used by Vazquez-Barquero et al (1992) as they rated only current physical illness of a non-transient nature (in fact, the majority of selected subjects reported chronic diseases); furthermore, although they selected subjects who scored over the threshold for 'caseness' on the GHQ, the GHQ score was not included in logistic regression analysis as a controlling variable.…”
Section: Physical Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research that adopts some version of this model has shown the importance of ' illness ' in studies of health services utilization (Bice et al 1972 ;Hershey et al 1975 ;Berki & Kobashigawa, 1976 ;Wolinsky, 1976 ;Kronenfeld, 1978 ;Va! zquez-Barquero et al 1992 ;Adler et al 1993 ;Feinstein, 1993 ;Goldberg, 1995, Himmelstein & Woolhandler 1995.…”
Section: Introductionmentioning
confidence: 99%
“…They usually do not need much encouragement to talk about somatic problems but are often reluctant to talk about nonmedical matters, either because they expect the doctor not to be interested in these matters, because of embarrassment and the fear of appearing foolish, or because of real anxiety about the possible significance of the symptoms (Roter & Hall, 1992). Even patients with serious psychological distress only present somatic problems during the consultation (Katon, Korff, &von Lin, 1990;Vasquez-Barquero, Diez Manrique, & Gaite, 1992;Verhaak & Tijhuis, 1994). As a consequence, general practitioners often do not recognize the patient's psYchosocial problems (Goldberg & Bridges, 1987;Ormel, van den Brink, & Koeter, 1990;Skuse & Williams, 1984)..This may lead to patient dissatisfaction, noncompliance, and even worsening health (Cassell, 1991;Roter & Hall, 1992;White, 1988).…”
mentioning
confidence: 99%